2020
DOI: 10.1021/acs.jafc.0c05205
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-propionic Acid Improved the Intestinal Barrier by Enhancing Epithelial Barrier and Mucus Barrier

Abstract: Destruction in intestinal barrier is concomitant with the intestinal diseases. There is growing evidence that tryptophan-derived intestinal bacterial metabolites play a critical role in maintaining the balance of intestinal mucosa. In this study, the Caco-2/HT29 coculture model was used to evaluate the effect of indole-3-propionic acid (IPA) on the intestinal barrier and explore its underlying mechanism. We found that IPA increased transepithelial electrical resistance and decreased paracellular permeability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 41 publications
3
88
0
Order By: Relevance
“… 2 IPA is similar in structure to melatonin. More and more studies have confirmed the beneficial effects of IPA on the intestines 30 and liver, 15 which are mainly manifested in stabilizing the intestinal mucosal barrier, regulating the intestinal flora, and interacting with the immune system to change intestinal biology properties, such as anti-inflammatory and anti-oxidant. Although previous research has proposed subtle differences in the chemical structure between melatonin and IPA and speculated the latter substance may have unfavorable effects, 10 , 17 , 18 there are no relevant reports so far.…”
Section: Discussionmentioning
confidence: 96%
“… 2 IPA is similar in structure to melatonin. More and more studies have confirmed the beneficial effects of IPA on the intestines 30 and liver, 15 which are mainly manifested in stabilizing the intestinal mucosal barrier, regulating the intestinal flora, and interacting with the immune system to change intestinal biology properties, such as anti-inflammatory and anti-oxidant. Although previous research has proposed subtle differences in the chemical structure between melatonin and IPA and speculated the latter substance may have unfavorable effects, 10 , 17 , 18 there are no relevant reports so far.…”
Section: Discussionmentioning
confidence: 96%
“…85 Feeding rats a high-fat diet damages the epithelial barrier, which is reversed by IPA treatment via increased Muc2 and Muc4 expression, which strengthen the mucosal layer. 86,87 In addition, IPA also up-regulates MUC2 expression in a colonic spheroid culture system. 88 A combination of Trp and Lactobacillus plantarum KLDS 1.0386 (high Trp-metabolic activity) treatment improved the epithelial and mucus barrier by decreasing the expression of proinflammatory cytokines (TNF-α, IL-1β, and IL-6) in adextran sodium sulfate (DSS)-induced colitis mouse model.…”
Section: Tryptophan Metabolitementioning
confidence: 99%
“…GF-mice colonization with an IPA-producing strain like C. sporogenes restores the IPA serum level [ 13 ]. It was shown to activate the AhR and the PXR pathways leading to the reduction of the symptoms in a mice-dextran sodium sulfate (DSS) model of colitis [ 157 , 158 ]. Thus, IPA might be an interesting candidate for the treatment of UC.…”
Section: Microbiota-derived Metabolites That Modulate Host Immunity In the Gutmentioning
confidence: 99%